PENDEKATAN PEMECAHAN MASALAH UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA SMK - Aminah Zuhriyah; Nurimani Nurimani (Sekolah Tinggi Pariwisata Mataram, 2021)
This article discusses the effect of problem-solving approaches to improve students' understanding of mathematical concepts. The purpose of this study was to determine the differences in understanding the mathematical concepts of students who learn to use a problem-solving approach with conventional methods in class X students of SMK Yatindo Bekasi. This study uses a quantitative approach and experimental methods. The research sample involved students of class X-2 as an experimental group learning using a problem-solving approach and class X-1 as a control group, each group totaling 30 students. The results of the research from testing the data analysis prerequisites included: the normality test using the Kolmogorov-Smirnov test for the experimental and control groups obtained by the same sig-count value, namely 0.200, meaning that the sig-count is greater than 0.05 sig-table, it is concluded that it is normally distributed, While the homogeneity test obtained the levene's test results with the sig-count value greater than the sig-table (0.109> 0.05). Then testing the hypothesis, obtained a sig-count value of 0,000 or a t-test value of 3,829> 2,000, the conclusion: there are differences in mathematical understanding of students who learn to use problem solving approaches with students who learn using conventional methods